PENGARUH RETURN ON ASSET, CURRENT RATIO, DEBT TO EQUITY RATIO, FIRM SIZE, DAN FREE CASH FLOW TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kamila Inez Fibriani; Amries R. Tanjung; Errin Yani Wijaya (Jurnal Ekonomi, 2014)
This research was conducted to examine the effect of return on assets, current ratio, debt to equity ratio, firm size, and free cash flow to dividend payout ratio on property and real estate companies listed on Indonesia Stock Exchange simultanously and partially. Data used in this research were secondary data collected from Indonesia Stock Exchange. The population included 40 property and real estate companies listed on Indonesia Stock Exchange in period of 2008-2012. Seven sample companies selected by purposive sampling method.To examine the effect of return on assets, current ratio, debt to equity ratio, firm size, and free cash flow to dividend payout ratio, a multiple linier regression analysis method was used, and the hypotheses were tested using a statistical test. The results showed that the coefficient of determination (R2) is 40.2%. This means that dividend payout ratio was affected by return on assets, current ratio, debt to equity ratio, firm size, and free cash flow by 40.2%. F Statistic test showed that five independend variables affected dividend payout ratio simulatanously. On the other hand, t statistic test indicated that only firm size affected partially to dividend payout ratio.